2015
DOI: 10.1159/000382130
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Relapses: Epidemiology, Outcomes and Management. A Systematic Review

Abstract: Relapses (episodic exacerbations of neurological signs or symptoms) are a defining feature of relapsing-remitting multiple sclerosis (MS), the most prevalent MS phenotype. While their diagnostic value relates predominantly to the definition of clinically definite MS, their prognostic value is determined by their relatively high associated risk of incomplete remission resulting in residual disability. The mechanisms governing a relapse incidence are unknown, but numerous modifiers of relapse risk have been desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 204 publications
(187 reference statements)
3
97
0
10
Order By: Relevance
“…Generally, observational data have found male sex, older age at onset, progressive state at onset and higher number of MRI lesions to be predictive of a poor prognosis with faster disability progression. 74,75 A recent systematic review has identified several key factors related to relapse frequency and recovery. 75 Relapse activity appears to decrease with age and disease duration and cohort studies suggest that women experience relapses more frequently.…”
Section: Risk Factors For Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, observational data have found male sex, older age at onset, progressive state at onset and higher number of MRI lesions to be predictive of a poor prognosis with faster disability progression. 74,75 A recent systematic review has identified several key factors related to relapse frequency and recovery. 75 Relapse activity appears to decrease with age and disease duration and cohort studies suggest that women experience relapses more frequently.…”
Section: Risk Factors For Disease Progressionmentioning
confidence: 99%
“…74,75 A recent systematic review has identified several key factors related to relapse frequency and recovery. 75 Relapse activity appears to decrease with age and disease duration and cohort studies suggest that women experience relapses more frequently. Modifiable risk factors, including smoking, exposure to infectious disease and discontinuation of DMTs, are also associated with increased relapse frequency.…”
Section: Risk Factors For Disease Progressionmentioning
confidence: 99%
“…Quality of life is reduced in patients with frequent relapses. The psychosocial burden due to relapse has a negative effect on social life and the family life of patients (6).…”
Section: The Definition and Features Of Relapsementioning
confidence: 99%
“…Higher number of relapses in the first years, polysymptomatic relapses, and pyramidal system, brain stem and spinal cord involvement are poor prognosis indicators. Conversely, sensory relapses, fewer relapses, and relapses with optic neuritis and recovery without sequelae are good prognostic features (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, women appear to be at greater risk than males (Ascherio et al, 2014; Belbasis et al, 2015; Lauer, 2010). Relapses predisposing risk factors have been investigated to a lesser extent and associations reported are discordant, namely young age, short MS duration, low serum vitamin D levels, smoking, psychological and other stress, vaccination, infections, post-partum, breast feeding and assisted reproduction (McKay et al, 2016; Kalincik, 2015). …”
Section: Introductionmentioning
confidence: 99%